Utilization of grazing in different small ruminant management systems on Crete Island, Greece - Voutzourakis N.; Tzanidakis N.; Butler G.; Leifert C.; Soritaki S.; Stefanakis A. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Two major small ruminant management systems exist on Crete, the semi-intensive (SI) and the extensive (EX). For the establishment of these systems the availability of pasture has a major impact. A project lasted from 2009 until 2012 aimed to study the characteristics of these systems and the impact on productivity, product quality and animal health. Twenty farms were selected, based on criteria established by an earlier survey, and were monitored for two milking seasons. At the extensive systems, located at the slope of the mountains, the animals graze almost exclusively on marginal communal pastures, where transhumant practices are still in place. The farmers use concentrate feeds and hay to increase productivity, mainly during milking period and during critical time-periods when grazing is scarce. The semi-intensive systems, are located at lower altitudes, where the animals graze mainly on fenced cultivated pastures and rotational grazing is applied. The use of concentrate feeds and hay is significant throughout the year. Between the two systems, the semi-intensive achieve higher production rates, but significant differences were also found for product quality, where extensive systems had in general a more preferable fatty acid profile.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)